2023
DOI: 10.1108/tr-02-2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

Can tourism curb income inequality? Tourism Agenda 2030

Abstract: Purpose This paper aims to examine the relationship between tourism development and income inequality, closely linked to the Sustainable Development Goals, for the case of a large sample of 83 countries (and subsamples) over the period 1990–2019. Design/methodology/approach This study uses rigorous dynamic panel data analysis, namely, a Panel Vector Autoregressive Error Correction model, which takes into account both dynamic and endogenous relationships in the tourism-inequality nexus. Findings The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…However, the results of squaring tourism income suggested that income inequality would be significantly reduced if tourism were to double its current level. Seetanah et al [54] studied 83 countries over the period 1990-2019 and found that tourism had a role in reducing income inequality (although relatively small). Moreover, the impact of tourism on income inequality was greater in developing and tourist-dependent economies than in developed economies.…”
Section: Synchronization Of Tourism Development and Poverty Reductionmentioning
confidence: 99%
“…However, the results of squaring tourism income suggested that income inequality would be significantly reduced if tourism were to double its current level. Seetanah et al [54] studied 83 countries over the period 1990-2019 and found that tourism had a role in reducing income inequality (although relatively small). Moreover, the impact of tourism on income inequality was greater in developing and tourist-dependent economies than in developed economies.…”
Section: Synchronization Of Tourism Development and Poverty Reductionmentioning
confidence: 99%
“…There seems to be no doubt about the role of the tourism sector in regional economic development, it is even the backbone of the economy in certain regions. For example, López-López et al (2006) from Los Cabos Mexico, Li et al (2016) from China, (Ibret et al, 2013;Uzar & Eyuboglu, 2019) in Türkiye, as well as Ioannides et al (2019) in the Netherlands and globally (Alam & Paramati, 2016;Brouder & Ioannides, 2014;Fang et al, 2020;Mahadevan & Suardi, 2019a;Nguyen et al, 2020a;Seetanah et al, 2023). Indonesia is one of the countries that relies on tourism as a driving sector of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the attendant literature on tourism development has largely focused on drivers of tourism in both developed and developing countries (Alvarez & Campo, 2014; Enders et al, 1992; Kingsbury & Brunn, 2004; Liu & Pratt, 2017; Mehmood et al, 2016; Pizam & Fleischer, 2002; Pratt & Liu, 2016; Richter & Waugh, 1986; Saha & Yap, 2014; Sönmez & Graefe, 1998; Sönmez et al, 1999), especially on the nexus between income inequality and tourism (Adeniyi et al, 2023; Chiu & Wang, 2023; Dossou et al, 2023; Kinyondo & Pelizzo, 2015; Kyara et al, 2023; Seetanah et al, 2023; Zhang & Yang, 2023). Unfortunately, in spite of the evolving literature on such determinants, we are unaware of a contemporary study that assesses how political stability and the rule of law moderate macroeconomic factors (such as domestic investment and trade openness) to influence tourism development.…”
mentioning
confidence: 99%